Mental fatigue impairs endurance performance: A physiological explanation - Martin, K.; Meeusen, R.; Thompson, K. G.; Keegan, R.; Rattray, B. (Sports Medicine, 2018)
Mental fatigue reflects a change in psychobiological state, caused by prolonged periods of demanding cognitive activity. It has been well documented that mental fatigue impairs cognitive performance; however, more recently, it has been demonstrated that endurance performance is also impaired by mental fatigue. The mechanism behind the detrimental effect of mental fatigue on endurance performance is poorly understood. Variables traditionally believed to limit endurance performance, such as heart rate, lactate accumulation and neuromuscular function, are unaffected by mental fatigue. Rather, it has been suggested that the negative impact of mental fatigue on endurance performance is primarily mediated by the greater perception of effort experienced by mentally fatigued participants. Pageaux et al. (Eur J Appl Physiol 114(5):1095-1105, 2014) first proposed that prolonged performance of a demanding cognitive task increases cerebral adenosine accumulation and that this accumulation may lead to the higher perception of effort experienced during subsequent endurance performance. This theoretical review looks at evidence to support and extend this hypothesis.